DEVELOPMENT OF SIMPLE GREEN SPECTROPHOTOMETRIC METHOD FOR DETERMINATION OF CEFOPERAZONE SODIUM AND CEFEPIME HYDROCHLORIDE IN BULK, PHARMACEUTICAL DOSAGE FORMS AND HUMAN URINE - M. HOSNY, MERVAT (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To evaluate a validated , simple,sensitive,inexpensive,green method for determination of cefoperazone Na and cefepime hydrochloridein pure form, pharmaceutical dosage form and human urine using ferric chloride and ferricyanide by spectrophotometry. Method:The estimation is based on the reduction of ferric ions in its salt form to ferrous ions by the drug, which in presence of potassium ferricyanide produces greenish blue colored chromogen measured at 766 nm against blank.The proposed method was applied to the determination of these drugs in pharmaceutical formulations and urine. Results: Beer's law was obeyed in the concentration range 0.8-8 Î¼g/mL, for both drugs, the limits of detection and quantificationwere reported. The intensity of the color in case ofcefoperazone Na increases with time at room temperature and so a kinetic method was developed for its determination. The results demonstrate that the method is equally accurate and precise as the reference methods as found from the t- and F-values. The reliability of the method was established by recovery studies using standard-addition technique. Conclusion:The proposed method has higher sensitivity than many of the reported methods, the method is green analytical methods so, it is inexpensive and ecofriendly. Moreover, the method doesn't require various elaborate treatments and tedious extraction procedures. Keywords: Kinetic determination; Spectophotometry;cefoperazone Na; Ferricyanide.